Variation in training requirements within general surgery: comparison of 23 countries. Issue 4 (11th June 2020) - Whewell, H; Brown, C; Gokani, V J; Harries, R L; Aguilera, M L; Ahrend, H; Al Qallaf, A; Ansell, J; Beamish, A; Borraez-Segura, B; Di Candido, F; Chan, D; et al.
Abstract: Background: Many differences exist in postgraduate surgical training programmes worldwide. The aim of this study was to provide an overview of the training requirements in general surgery across 23 different countries. Methods: A collaborator affiliated with each country collected data from the country's official training body website, where possible. The information collected included: management, teaching, academic and operative competencies, mandatory courses, years of postgraduate training (inclusive of intern years), working-hours regulations, selection process into training and formal examination. Results: Countries included were Australia, Belgium, Canada, Colombia, Denmark, Germany, Greece, Guatemala, India, Ireland, Italy, Kuwait, the Netherlands, New Zealand, Russia, Saudi Arabia, South Africa, South Korea, Sweden, Switzerland, UK, USA and Zambia. Frameworks for defining the outcomes of surgical training have been defined nationally in some countries, with some similarities to those in the UK and Ireland. However, some training programmes remain heterogeneous with regional variation, including those in many European countries. Some countries outline minimum operative case requirement (range 60–1600), mandatory courses, or operative, academic or management competencies. The length of postgraduate training ranges from 4 to 10 years. The maximum hours worked per week ranges from 38 to 88 h, but with no limit in some countries. Conclusion: Countries have specific and often differing requirements of their medical profession. Equivalence in training is granted on political agreements, not healthcare need or competencies acquired during training. Graphical Abstract: Many differences exist worldwide in postgraduate surgical training programmes. Countries have specific and often differing requirements of their medical profession. Equivalence in training is granted on political agreements, not healthcare needs or competencies acquired during training. Wide variation between countries